RESPON MASYARAKAT TERHADAP PENGOBATAN ALTERNATIF TRADISIONAL PONDOK MIFTAHUSSYIFA DI KOTA PEKANBARU - Riri Rahma Andriani; Yoserizal " (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
The phenomenon that occurs is the increasing number of people who seek treatment at the alternative traditional medicine at Miftahussyifa Pondok in Pekanbaru City. The purpose of this study is (1) To find out the response of the people who have participated in traditional alternative medicine at Miftahussyifa hut. (2) To find out the factors that encourage them to seek treatment in traditional alternative medicine at the Miftahussyifa hut. This study uses the percentage frequency obtained from the results of the questionnaire. The sample in this study was 89 respondents. The results of the study found that the public perception index of Traditional Alternative Medicine in Pondok Miftahussyifa was 75.12% and classified as a good category. Many factors cause people to seek treatment in alternative medicine including social, economic, cultural, psychological factors, saturation of services, benefits and success and knowledge. Keywords: Response, Alternative Medicine, Miftahussyifa